Program Pendampingan Badan Usaha Milik Desa Menuju Ekonomi Mandiri Di Desa Labuh Air Pandan Kecamatan Mendo Barat Kabupaten Bangka - sumiyati; Maya Yusnita (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
This community service program is an activity by applying knowledge to the Village-Owned Enterprises (BUMDES) Labuh Air Pandan, Mendo Barat District, Bangka Regency. The aim is to provide assistance in product creation and BUMDES financial governance. The method of implementing this activity uses the method of practice and demonstration which is manifested in three main programs. The first and second programs use a practical method by providing training that invites participants to directly process caught fish that do not pass the market into crispy fish snack products and fish sauce. The third program with a demonstration method in the form of assistance in the preparation of BUMDES financial reports. Indicators of program success are the availability of packaged finished products and BUMDES financial reports. Overall, the success of this program has reached 70% in its implementation because it has produced products. The activity is still in the form of a sample product and to evaluate the impact of the ability of BUMDES managers in compiling financial reports, it must be carried out more than the time required for this community service activity.